2009
DOI: 10.1007/s10339-009-0342-3
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of brain processes supporting meditation

Abstract: Meditation is an ancient spiritual practice, which aims to still the fluctuations of the mind. We investigated meditation with fMRI in order to identify and characterise both the "neural switch" mechanism used in the voluntary shift from normal consciousness to meditation and the "threshold regulation mechanism" sustaining the meditative state. Thirty-one individuals with 1.5-25 years experience in meditation were scanned using a blocked on-off design with 45 s alternating epochs during the onset of respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 67 publications
7
68
1
1
Order By: Relevance
“…This reduced activation in the right MPFC is consistent with findings from Baerentsen et al (2010), who reported deactivation of this cortical region during sustained meditation. Additionally, our findings are in line with a study conducted by Kross and colleagues (Kross et al, 2009) investigating the relationship between brain function and the acceptance of emotional states.…”
Section: Brain Patterns Related To Mindfulness In Experienced Meditatsupporting
confidence: 91%
“…This reduced activation in the right MPFC is consistent with findings from Baerentsen et al (2010), who reported deactivation of this cortical region during sustained meditation. Additionally, our findings are in line with a study conducted by Kross and colleagues (Kross et al, 2009) investigating the relationship between brain function and the acceptance of emotional states.…”
Section: Brain Patterns Related To Mindfulness In Experienced Meditatsupporting
confidence: 91%
“…Rao and Paranjpe (2008, p. 188) tried to coin the expression "passive diffused attention or inattention" when referring to meditation. Baerentsen et al (2010) refer to meditation as the control of fluctuations of the mind that aim to still the fluctuations (patterning) of the mind. These authors are naturally referring to the effects and not to the technique, and offer a confusing understanding to its readers.…”
Section: Followingmentioning
confidence: 99%
“…The research reports on meditation in this issue (Baerentsen et al 2010;Baijal and Srinivasan 2010;Cahn et al 2010;Travis et al 2010) investigate the neural changes as the practitioners meditate in the laboratory (Tagini and Raffone's article in this issue presents a related theoretical development). These studies employ both FA and OM meditation types.…”
Section: States and Traits In Neuroscientific Studies Of Meditationmentioning
confidence: 99%
“…The fMRI investigation by Baerentsen et al (2010) elucidates fundamental aspects of meditation practice beyond specific styles, with a view of meditation as a practice to still the fluctuations of the mind, with reference to Patanjali's classical analysis of yoga. Baerentsen et al's study reveals distributed deactivation and activation patterns in the brain, in both cortical and subcortical regions, characterizing switching into the meditation state and sustaining it.…”
Section: States and Traits In Neuroscientific Studies Of Meditationmentioning
confidence: 99%